Pattern of Carbapenem Resistance in Enterobacteriaceae in Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2020)
The global emergence and spread of Carbapenem Resistant Enterobacteriaceae have been threatening the ability to treat an infection. Hence the present study was carried out with the aim to isolate important members of Enterobacteriaceae family with identification of carbapenem resistant isolates among them. The study was done in the Department of Microbiology, Rajshahi Medical College with collaboration of different disciplines of RMCH from January 2019 to December 2019. Samples were collected purposively. Causative organisms were isolated by culture and identified by colonial morphology, gram staining and relevant biochemical tests. Identified Enterobacteriaceae those showed resistance to carbapenem (imipenem, meropenem) were tested phenotypically by Modified Hodge Test (MHT) to see carbapenemase production. A total of 97 Enterobacteriaceae were isolated from 275 samples. E. coli (54.64%) was the most frequent isolate. By Modified Hodge Test, 19(19.59%) bacteria were phenotypically confirmed as Carbapenem Resistant Enterobacteriaceae (CRE). This study signifies that carbapenem resistance is increasing at an alarming rate.TAJ 2020; 33(2): 63-68